Manajemen Keuangan Sekolah: Transparansi dan Akuntabilitas dalam Pengelolaan Dana - Rahma Adzkia; Friska Anastasya; Nur Syahda Awalliyah; Hesti Kusumaningrum (Pendidikan Al-Gafari, 2024)
This research explores the importance of transparency and accountability in school financial management, especially in fund management. In the educational context, effective financial management not only ensures the continuity of school operations, but also influences the quality of education provided to students. This study uses a qualitative approach with case study methods in several schools that have implemented transparent and accountable financial management. The research results show that disclosure of financial information to all stakeholders, including parents and the community, is very important in building trust and active participation. In addition, accountability in managing school funds is achieved through clear reporting mechanisms, internal and external audits, and the involvement of the school finance committee in decision making. These findings confirm that transparency and accountability are not just administrative requirements, but are also the foundation for effective and efficient financial management. With transparency, schools can avoid misuse of funds and improve the quality of educational services. The conclusion of this article recommends implementing policies that support transparency and accountability in school financial management to achieve better educational goals.